1998
DOI: 10.1016/s0006-3223(97)00399-5
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability as an index of cue reactivity in alcoholics

Abstract: HRV paradigm appears more sensitive than MHR to measure cue reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…Kaplan et al, 1983;McCusker and Brown, 1991;Kaplan et al, 1985;Cooney et al, 1997;Glautier and Drummond, 1994;McCaul et al, 1989aMcCaul et al, , 1989bStormark et al, 1995], although their experimental designs, including cues, induction methods, and features of participants differ from one another. Rajan et al [1998] even deemed it as a reliable indicator of cue reactivity. Nevertheless, the studies of Pomerleau et al [1983], Eriksen and Goetestam [1984], and Greeley et al [1993] implicate either no elevation or reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan et al, 1983;McCusker and Brown, 1991;Kaplan et al, 1985;Cooney et al, 1997;Glautier and Drummond, 1994;McCaul et al, 1989aMcCaul et al, , 1989bStormark et al, 1995], although their experimental designs, including cues, induction methods, and features of participants differ from one another. Rajan et al [1998] even deemed it as a reliable indicator of cue reactivity. Nevertheless, the studies of Pomerleau et al [1983], Eriksen and Goetestam [1984], and Greeley et al [1993] implicate either no elevation or reduction.…”
Section: Discussionmentioning
confidence: 99%
“…11,25,26,36,59]; their experimental designs, including features of subjects, cues, induction methods, differ from one another though. Therefore, heart rate is frequently deemed as a reliable indicator of cue reactivity in alcoholics [50]. Greeley et al [20], Eriksen and Gotestam [14] and Pomerleau et al [46] had yet converse implications.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, certain diseases such as hypertension Novak et al 1994), diabetes Bernardi et al 1992), or coronary heart disease (Krittayaphong et al 1997;Stein et al 2000) would cause HRV to decrease. Moreover, as to lifestyle, some studies reported that smoking (Barutcu et al 2005), drinking habits (Rajan et al 1998), or exercise habits (Myslivecek et al 2002) affect HRV. In the present study, confirmed by the annual health examination, participants did not have a history of the above diseases in the present or past.…”
Section: Potential Confounders Of Hrv Changesmentioning
confidence: 99%